Mechanical Behaviour of Materials, Stress analysis and Mohr′s circle
Este conjunto de animaciones explica cm̤o emplear el cr̕culo de Mohr para anl̀isis de tensin̤. Comprende los siguientes elementos:Typical stress-strain curve for a polycrystalline sampleStress tensor related to definition of the orthogonal x1, x2 and x3 axesMohr<U+0092>s circle method: an element under a stress stateMohr<U+0092>s circle method: an interactive plot toolCalculation of the yield criteria for metalsCalculation of the yield criteria for non-metals